Report on professional attachment with Deutsche Morgan Grenfell Asia Pacific holdings. - Goh, Thong. (2009)
This report will provide a documented account of the work done in the 8 weeks attachment with Deutsche Morgan Grenfell Asia Pacific Holdings, and how theoretical knowledge in University was applied in practice.